Phytonutrients - Salter, Andrew; Tucker, Greg; Wiseman, Helen (Wiley-Blackwell, 2012)
In many Western diets, the role of plants has been reduced in favour of more animal-based products and this is now being cited more widely as being the cause of increases in the incidence of diseases such as cancer and cardiovascular disease